Single-cell transcriptomics of human T cells reveals tissue and activation signatures in health and disease - Peter A. Szabo (Nature Portfolio, 2019)
Immune cells are shaped by the tissue environment, yet the states of healthy human T cells are mainly studied in the blood. Here, the authors perform single cell RNA-seq of T cells from tissues and blood of healthy donors and show its utility as a reference map for comparison of human T cell states in disease.